Saúde mental e pandemia: um estudo com os professores do Ensino Fundamental – Anos Iniciais do Município de Cascavel/PR - Rocha, Geovane dos Santos da (2021)
The pandemic caused by COVID-19 triggered off, in the years 2020 and 2021, several changes in the Brazilian reality, including in the ways of carrying out the activities of school institutions. Due to the need to establish measures of social isolation, remote teaching became the main means of exercising pedagogical mediations. Considering the particularities of this context, this study sought to understand how the COVID-19 pandemic period affected the mental health of teachers of the Elementary School – Initial Years in the city of Cascavel/PR. Thereunto, it was developed a research with three methodological procedures: theoretical-bibliographic review based on Historical-Cultural Psychology and Psychoanalysis; documentary survey of the main legislative acts related to remote teaching in Cascavel/PR; and a field research. To carry out the field research, it was designed a questionnaire with open and closed questions, which dealt with professional and subjective aspects experienced at the time of the pandemic. 170 teachers from 20 schools participated in the study, making up a sample of 10.8% of all professionals. From the collected answers, we performed data analysis with the intermediation of qualitative procedures, following the steps of thematic/category analysis, and quantitative, through statistical analysis. To discuss the results, four axes were defined: professional activities, realities experienced, impacts on the teachers‟ psyche and perspectives for the post-pandemic. Following these axes, we interpreted the information with the aid of the theoretical-bibliographic review of the study. As a result, it was uncovered that the professional activities developed by teachers during the pandemic period had negative repercussions on the emotional aspect, since the pedagogical practices distanced themselves from the social function of the school (promote the appropriation of students' knowledge and the role of mediation of the teacher), relating in greater proportion to the fulfillment of bureaucratic tasks and the mechanical reproduction of content. We also noticed an increase in activities performed, not only professional, but also at home and personal. As a result, they started to present feelings of exhaustion and fear of noncompliance with activities, both in relation to students and close people (children and family members). These factors caused some symptoms, especially related to anxiety (irritability, nervousness, anguish, physical symptoms, fear of dying etc.) and depressed mood (sadness, low self-esteem, feelings of guilt, worthlessness etc.), besides of a few miscellaneous ones, such as insomnia, frustration and suicidal ideation. Almost 90% of teachers claimed to have felt, in some way, the repercussions of the pandemic period, such as the importance of the physical presence of the teacher, the influence of the mental health status on the performance of activities and the necessity of professional support. From that, we concluded that the period of the COVID-19 pandemic had repercussions on the mental health of teachers to varying degrees, depending on the subjectivity of each person and how each one internalized these events.